Linkage between endosomal escape of LNP-mRNA and loading into EVs for transport to other cells - Marco Maugeri (Nature Portfolio, 2019)
Lipid nanoparticles (LNPs) are potential platforms for RNA-based therapeutics, but the fate of LNP-RNAs upon internalization into the cell is unclear. Here, the authors show that LNP-mRNAs and ionizable lipids escape the endosomes and are re-released via extracellular vesicles which could deliver the functional mRNA to other cells.